Local Government Audit Committees: A Behaviour Framework for Effective Audit Committee Performance. Issue 2 (30th March 2018) - Thomas, Keith; Purcell, Aquinas J.
Abstract: Stakeholders will always be more receptive to the creation of structured and credible systems that pull participants towards good governance outcomes which serve to remove temptation rather than systems that attempt to push or otherwise coerce people into a state of compliance. This paper uses behavioural theory as an interpretative lens to explain the actions and effectiveness of public sector audit committees. Financial probity, independence to avoid conflicts of interest and conformance to ethical practices are the tenets of effective governance. Audit committees can be one of the mechanisms to monitor the risks of the public sector and the executive management team especially where 'self‐interest' conflicts with the governance requirements of legislation, societal norms and community expectations. An effective audit committee can provide behavioural oversight of governance processes, although one cannot legislate for integrity and honesty. The presence of an effective and contributing audit committee in local government negates a councillor from listening or subverting positive actions and provides a signal to external stakeholders of organisational risks. Abstract : Stakeholders will be more receptive to the creation of credible governance systems which serve to remove temptation rather than those that attempt to bludgeon people into a state of compliance. This paper discusses behavioural theory to explain the interactions and outcomes of audit committees. These theories provide the interpretative lenses through which to assess the effectiveness of local government audit committees.